Effects of combined plyometric and sled training on vertical jump and linear speed performance ​​in young soccer players (Efectos de la combinación de entrenamiento pliométrico y de arrastres sobre el rendimiento en salto vertical y la velocidad lineal e - Moisés Falces-Prieto; Javier Raya-González; Eduardo Sáez de Villarreal; Jesús Rodicio-Palma; Francisco Javier Iglesias-García; Francisco Tomás González Fernández (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación, 2021)
The objective of this study was to evaluate the effects of a combined plyometrics and sled training carried out two days a week for 8 weeks. 60 young male soccer players were distributed in 4 groups (Under U16) [Experimental Group (U16 Exp, n=15) and Control Group (U16 Cont, n=15); and (Under19) [U19 Exp, (n=15) and U19 Cont, (n=15)]. The jump with countermovement (CMJ) was evaluated with Chronojump-Boscosystem® and the time in seconds (sec) in the 10, 20, and 40 m split with FitLight Trainer®. Was calculated a level of significance of p≤0.05, the effect size (ES) and % change. Both experimental groups improved from pre-to pots-test in CMJ [U16Exp (p<0.02) and U19Exp (p<0.01)] and the 10, 20, and 40 m splits [U16Exp (p<0.02, p<0.03, and p<0.01, respectively) and U19Exp (p<0.02, p<0.02, and p<0.01, respectively)]. Therefore, the combination of football and plyometric and resisted methods can be used for a general development of the neuromuscular capacities of young soccer players.